2017
DOI: 10.1097/md.0000000000007143
|View full text |Cite
|
Sign up to set email alerts
|

Lymph node metastasis characteristics of papillary thyroid carcinoma located in the isthmus

Abstract: The frequency and pattern of lymph node metastasis and the extent of dissection for isthmic papillary thyroid carcinoma (PTC) remain unclear, and the aim of this present study was to evaluate these characteristics and to attempt to detect the best surgical protocol for isthmic PTCs. A total of 3185 consecutive patients with PTCs were reviewed. Of these patients, 47 with a single isthmic PTC were enrolled in our study, and matched 47 patients with a single PTC located in the unilateral lobe were randomly select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 29 publications
3
25
1
Order By: Relevance
“…Previous studies have reported that patients with PTC located in the isthmus are more likely to have CLNM, especially pretracheal and prelaryngeal LNM, and bilateral CCND should be considered. [34][35][36] According to this study, male sex (p=0.005, OR=17.545) and the presence of an aggressive pathology (p=0.027, OR=48.063) were independent predictive factors of contralateral paratracheal LNM. Men are known to be at high risk for thyroid cancer.…”
Section: Discussionmentioning
confidence: 61%
“…Previous studies have reported that patients with PTC located in the isthmus are more likely to have CLNM, especially pretracheal and prelaryngeal LNM, and bilateral CCND should be considered. [34][35][36] According to this study, male sex (p=0.005, OR=17.545) and the presence of an aggressive pathology (p=0.027, OR=48.063) were independent predictive factors of contralateral paratracheal LNM. Men are known to be at high risk for thyroid cancer.…”
Section: Discussionmentioning
confidence: 61%
“…In the literature, malignancy rate in isthmus region was reported between 1% and 17.4% in different studies (7,9,10,(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). In a study including 557 nodules with definitive cytologic diagnoses, although isthmic nodules had lower malignancy rate (2.5%), the rate was not significantly different in the isthmus, right (9.6%), or left lobe (7.2%) (8).…”
Section: Discussionmentioning
confidence: 97%
“…Prevalence of thyroid nodules located in isthmus was found as 4.2-6.4% (7,9,11). The incidence of isthmic papillary thyroid cancer (PTC) ranges from 1% to 12.3% in different studies (12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Although PTC had an indolent course, isthmic PTCs were reported to have more aggressive behaviour, including multifocality, capsular invasion, and frequently having metastasis to lymph nodes in some studies (12,16).…”
Section: Introductionmentioning
confidence: 99%
“…4,[12][13][14]17,19 However, there are no specific data available in the literature for the management of WDTC confined to the thyroid isthmus with a long-term follow-up. 4,[12][13][14]17,19 However, there are no specific data available in the literature for the management of WDTC confined to the thyroid isthmus with a long-term follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Total thyroidectomy has been practiced for patients with WDTC located in the isthmus at many institutions. 4,[12][13][14]17,19 However, there are no specific data available in the literature for the management of WDTC confined to the thyroid isthmus with a long-term follow-up. 5 Current guidelines, including the 2015 ATA guidelines, 6 Korean Thyroid Association Guidelines, 7 Korean Association of Thyroid and Endocrine Surgeons Guidelines, 8 and British Thyroid Association guidelines 9 do not mention isthmusectomy as an acceptable procedure in the management of WDTC.…”
Section: Discussionmentioning
confidence: 99%